THE IMPACT OF REGISTERED NURSE WORK ENVIRONMENT ON CARE QUALITY IN NURSING HOMES. (16th November 2018) - White, E; Aiken, L; Aiken, M
Abstract: Registered nurses (RNs) provide vital leadership, care coordination, and surveillance in nursing homes to ensure that residents receive safe and appropriate care. The ability of RNs to perform these roles effectively is largely influenced by the organizational environment in which they practice. Extensive evidence from hospitals has shown that RN work environment is an important predictor of care quality, but very little research has explored this same relationship in nursing homes. In this study we examined the empirical relationship between RN work environment and care quality in nursing homes, using a cross-sectional secondary data analysis of 2015 RN4CAST four state nurse survey data; LTCfocus, a publicly available dataset from Brown University; and Nursing Home Compare. The sample consisted of 245 nursing homes in California, Florida, New Jersey, and Pennsylvania. Compared to nursing homes with poor RN work environments, facilities with good work environments had a 3.3% higher odds of receiving a Nursing Home Compare overall star rating of 4 or 5 stars versus 1 or 2 stars (OR=3.30, SE=1.58); 0.15 fewer hospitalizations per resident year (15 fewer hospitalizations per 100 residents per year) (β= -0.15, SE=0.08); and 1.8% fewer high risk residents with pressure ulcers (β= -1.81, SE=0.74). Nursing homes with good work environments also had fewer 30 day readmissions and fewer long-stay residents on antipsychotic medications, but these results were not statistically significant. Findings from this study suggest that nurse work environment is an important and tangible area to target for interventions to improve care quality in nursing homes.